(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article investigates the comparative-functional features of incomplete sentences in dialogic speech, focusing on English and Uzbek examples. Dialogic speech, characterized by its spontaneous and interactive nature, often includes incomplete sentences as a means of conveying meaning efficiently and effectively. By analyzing examples from both languages, we aim to identify similarities and differences in the use, structure, and functions of incomplete sentences.